If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15p + -30 = 0 Reorder the terms: -30 + 15p = 0 Solving -30 + 15p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + 15p = 0 + 30 Combine like terms: -30 + 30 = 0 0 + 15p = 0 + 30 15p = 0 + 30 Combine like terms: 0 + 30 = 30 15p = 30 Divide each side by '15'. p = 2 Simplifying p = 2
| -10x=-24 | | 8-4/x-2=-1/2 | | x+12x=-32 | | 11r=13-2 | | -15x+54=0 | | -3n+2=0 | | 2/5r=13-4r2 | | 1/12m−1/6=1/4m+12 | | t-79=184 | | 8p+10=-4+6 | | 3/4x^2-7x+9 | | -2+8y=-6 | | 15a/25a | | (x+3)(4x-16)=0 | | 2/5h-7=13 | | Y=-2x^2-12x-23 | | 1.875=5/8(b-5) | | 12x+16=31 | | b/3=3 | | u/8=2 | | 6(y-3)=2(19-y) | | c-9=3/4c | | t/4=32 | | 2y-(13-2y)=59 | | (x+2)+y= | | 6r+4s= | | (143(5)+67)=5 | | y^2-1y-42=0 | | 5/3+6/10 | | 4(2x-5)=16 | | 1/4(9x+3)=3x+1 | | 3x(x+7)=21 |